(untitled) (Research, Society and Development, 2021)
Plants have been seen as alternatives for researching natural antimicrobials and herbicides. The aim of this work was to evaluate the antibacterial, antifungal, and allelopathic properties of leaves extracts of Myrcia hatschbachii. The crude extract and fractions were obtained by Soxhlet apparatus. Antimicrobial activity was determined by the minimum inhibitory concentration (MIC) using the broth microdilution method. The ethyl acetate fraction showed activity against Candida albicans (MIC: 62.5 µg/mL), Staphylococcus aureus (MIC: 500 µg/mL), and Pseudomonas aeruginosa (MIC: 1000 µg/mL). Allelopathic activity evaluated the influence of crude extract and fractions on the germination and growth of Lactuca sativa. The crude extract and the chloroform fraction inhibited the growth of the radicle, while the hexane fraction inhibited the growth of the hypocotyl and radicle of lettuce seeds in all concentrations (100-1000 μg/mL). The biological potential of the species motivates further study of new antimicrobial and bioherbicidal agents.